Attitudes of Primary School Children with Hearing Impairment toward Visual Arts and School Refusal Tendencies in an Inclusive Education Setting in Calabar Education Zone, Nigeria - Ewa, James Abua; Nanjwan, J. D. (NIU Journal of Humanities, 2019)
This study was conceived to examine the relationship between attitudes of primary school pupils with hearing impairment toward the study of visual art and school refusal tendencies in Calabar Education Zone. To achieve the purpose of the research, two null hypotheses were formulated to guide the study. Literature was reviewed according to the variables. The correlation research design was adopted to execute the study. This design was chosen because it sought to establish the relationship between attitudes of primary school pupils with hearing impairment toward the study of visual art and school refusal tendencies among school age children in Calabar Education Zone. The population consisted of primary school children with hearing impairment. A sample size of One Hundred and Forty (140) pupils was randomly drawn from twenty inclusive education primary schools in the zone. A four point Likert-like questionnaire scale was used by the teachers to rate the pupils in order to extract information from the subjects under study. The instruments were validated by experts in research and special education. The reliability estimate of the instrument was established through test re-test split half method and the reliability index was found to be high. Pearson Product Moment Correlation Analysis was used to analyze the data collected. The result of the analysis revealed that there is a significant relationship between pupils’ interest and classroom participation in visual art and school refusal tendencies among school age children with hearing impairment. Based on the result obtained, conclusion was drawn and recommendations made. Keywords: School refusal tendencies, visual arts, pupils with hearing impairments, inclusive education setting.